Teachers’ emotional training and management of their classroom atmosphere - Barrientos, Amelia; Sánchez, Roberto; Arigita, Amaya (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This research article has as its starting point the educational and mentality paradigm in today's society, in which teachers have been in need of developing skills. The overall objective of the study is to know the relationship between the emotional intelligence—training that teachers should have—and their ability to manage the emotional and social climate of the classroom. The research methodology is descriptive. The results show that teachers perceive that they have not been instructed in emotional skills and, therefore, they feel the need to be trained in social-emotional skills in order to be able to manage classes in a positive way.